A high-temperature semiconductor catalyst and its application
A high-temperature semiconductor catalyst using silicon nitride and transition metals addresses inefficiencies in CO2 reduction by maintaining structural stability and catalytic activity, achieving efficient CO2 conversion to high-value hydrocarbons.
Patent Information
- Application Number
- CN202211741355.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-31
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-12-31
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photocatalytic reduction of CO2, and specifically relates to a high-temperature semiconductor catalyst and its application in the technical field of photocatalytic reduction of CO2. Background Art
[0002] With the development of economy and society, people's demand for energy is increasing day by day. Fossil energy and mineral energy, as the main energy sources, have brought inevitable environmental problems and caused energy crisis. CO2 emitted by the burning of fossil fuels has broken the balance of carbon cycle in nature, resulting in a continuous increase in the concentration of CO2 in the atmosphere, and the impact of greenhouse effect on human life has become more and more prominent.
[0003] Developing new energy is one of the keys to solving the energy crisis. As one of many energy sources, solar energy has a huge energy reserve and has been widely regarded as one of the solutions to save mankind from the impending energy shortage and environmental problems caused by the use of fossil fuels. The exploration of photocatalytic technology is of great significance to the energy industry.
[0004] Photocatalytic technology has been explored since the end of the last century. In 1972, Japanese scholar Honda-Fujishima discovered that photocatalytic technology can be used to decompose water to produce hydrogen. Since then, photocatalytic technology has attracted the attention of many researchers. Nowadays, using sunlight, an abundant, clean and renewable energy source, and using CO2, the main component of greenhouse gases, as a carbon source to reduce CO2 to high value-added products can not only turn waste into treasure and obtain clean energy, but also eliminate harm to the environment and reduce the negative impact of the greenhouse effect.
[0005] Reducing artificial CO2 by using sunlight similar to natural photosynthesis is a straightforward way to reduce greenhouse gases and provide sustainable energy to human society. While this concept seems to be a simple solution to the serious problem of energy shortage, the problems it faces are very complex, resulting in a process that is too inefficient to be practical in the short term.
[0006] New alternative photocatalysts are the key to solving such problems. In recent years, most literature has involved the optimization of photocatalytically active materials, but people have always focused on photocatalytically active materials that can perform at relatively low temperatures, and not enough attention has been paid to photocatalytically active materials that can perform at higher performance under the simultaneous action of light and heat. Fortunately, some people have realized this in recent years, and photothermal catalysis has entered the field of vision of mainstream researchers. The behavior of some photocatalysts under photothermal conditions has been studied, but due to limited time, people have not yet realized that photothermal catalysts need to have a certain tolerance to temperature. In order to maintain photoactivity at high temperatures, high-temperature semiconductors are needed as the basis of the catalyst. As one of the third-generation high-temperature semiconductors, silicon nitride material can maintain structural stability at high temperatures, has a stable physical structure and chemical properties, and is expected to exhibit quite outstanding photocatalytic activity at high temperatures. The stability of the structure is also of great significance to its reusable performance.
[0007] Due to the unique properties of silicon nitride, it has been widely used in the field of semiconductor electronic devices and has also been initially used in the field of catalysts. For example, CN202210025266 discloses a catalyst that uses it as a carrier for catalytic hydrogenation reactions. However, this is only the basic property of its high specific surface area, and there has been no report on its use in photocatalysis.
[0008] Based on this, the present invention proposes a novel photocatalyst that uses one or more of the elements such as copper, iron, cobalt, and ruthenium as active components and is composited with silicon nitride high-temperature semiconductor. This photocatalyst material uses high-temperature semiconductor Si3N4 as a carrier and one or more of the elements such as copper, iron, cobalt, and ruthenium as active components. It can still exert excellent catalytic performance under high temperature conditions, achieve higher solar energy utilization efficiency and CO2 conversion rate, and convert CO2 into hydrocarbons with high added value. Summary of the invention
[0009] The purpose of the present invention is to provide a new type of high-temperature semiconductor catalyst that can withstand temperature and has excellent catalytic efficiency in response to the needs of the background technology. The preparation process of the present invention is simple, environmentally friendly, and low in cost. It is a high-temperature semiconductor material worthy of in-depth exploration in the laboratory. At the same time, the catalyst material has high catalytic activity and stability.
[0010] The present invention discloses a method for preparing a high-temperature semiconductor catalyst using silicon nitride as a carrier and one or more of the elements such as copper, iron, cobalt, and ruthenium as active components. The method firstly calcines the semiconductor to remove impurities, then uses a photothermal assisted spraying method to load the active ions onto the carrier surface, further uses an ultrasonic method to improve the ion dispersion, and finally calcines to obtain the target catalyst. The specific steps are as follows:
[0011] To achieve the above object, the present invention adopts the following technical solution:
[0012] The present invention provides a high-temperature semiconductor catalyst, which is prepared by the following method:
[0013] Placing Si3N4 at a focal position under a xenon lamp light source, spraying an aqueous solution of a transition metal salt onto the surface of the Si3N4 under a first irradiation to obtain the sprayed Si3N4; subjecting the sprayed Si3N4 to ultrasonic treatment for 20-40 minutes, continuing to place the sprayed Si3N4 at a focal position under a xenon lamp light source, irradiating it for a second time for 10-20 minutes, and calcining it at 300-500°C for 1-3 hours (preferably 400°C for 2 hours) in a muffle furnace to obtain the high-temperature semiconductor catalyst;
[0014] The transition metal salt contained in the aqueous solution of the transition metal salt is nitrate, and the theoretical mass of the transition metal contained in the aqueous solution of the transition metal salt is 0.2%-0.5% (further 0.3%-0.4%) of the total mass of the theoretical mass of the transition metal contained in the aqueous solution of the transition metal salt and the mass of Si3N4.
[0015] Furthermore, the Si3N4 is β-phase Si3N4 with a particle size of 1 to 3 μm. Furthermore, the Si3N4 has been pretreated as follows: calcined at 500°C in a nitrogen atmosphere for 2 hours to remove gas impurities adsorbed from the air since leaving the factory.
[0016] Preferably, the total concentration of the transition metal salt in the aqueous solution of the transition metal salt is 0.01-0.1 mol·L -1 .
[0017] Furthermore, the transition metal contained in the aqueous solution of the transition metal salt is one or more of Fe, Cu, Co and Ru, preferably Ru.
[0018] Furthermore, the ultrasonic time is 30 minutes.
[0019] In one embodiment of the present invention, the power of the xenon lamp light source is 1000W, and the power only affects the drying time but does not affect the catalytic performance.
[0020] In one embodiment of the present invention, the second irradiation time is 10 minutes.
[0021] The prepared M(NO3)2 solution is sprayed onto the Si3N4 surface in small amounts and multiple times to load the active components on the semiconductor surface and remove excess moisture; the ratio of the metal content in the sprayed M(NO3)2 solution to the mass of the carrier is controlled to be between 0.2% and 0.5%, that is, the metal loading amount is between 0.2% and 0.5% (in heterogeneous catalysis, the loading amount is defined as = the mass of the metal active component / (the mass of the metal active component + the mass of the carrier)).
[0022] If the calcination temperature is too high and the time is too long, the active ingredients will aggregate and affect the catalytic performance; if the calcination temperature is too low and the time is too short, nitrate residues will remain and the catalytic performance will be reduced. It should be noted that the anion of the salt can only be nitrate, and other anions are difficult to remove and affect the activity. For example, sulfate salts may even make the catalyst toxic.
[0023] In addition, the present invention also provides an application of the above-mentioned high-temperature semiconductor catalyst in the photothermal catalysis of CO2 and water to produce methane.
[0024] Specifically, the application is: using a xenon lamp as a light source, focusing light in a closed reactor using a lens, using CO2 and water as reactants, and reacting to generate methane under the high-temperature semiconductor catalyst.
[0025] Furthermore, the light source is a 1000W xenon lamp, and the surface temperature of the high-temperature semiconductor catalyst can reach up to 350°C.
[0026] Furthermore, the gas pressure of CO2 in the closed reactor is 0.1 MPa.
[0027] Furthermore, the temperature of introducing CO2 is 250°C and the reaction time is 3 hours.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] A new, practical and efficient high-temperature semiconductor catalyst and its application in CO2 reduction reaction are provided. Focusing on the influence of temperature on catalyst performance, a high-temperature semiconductor is provided to increase the upper limit of the working temperature of the catalyst and expand the light absorption range; compared with traditional photocatalysts, it can withstand higher working temperatures, complete catalyst activation at high temperatures, and achieve a CO2 conversion rate of 0.1% and a solar energy conversion rate of 1.4% at high temperatures. It has higher carbon dioxide conversion efficiency, solar energy utilization rate and carbon dioxide conversion rate, and can convert carbon dioxide into more high-value alkane products. DETAILED DESCRIPTION
[0030] The preparation and application of the catalyst material in the present invention are further described below through specific examples, the purpose of which is only to better understand the content of the present invention but not to limit the protection scope of the present invention.
[0031] Embodiment 1:
[0032] a. Take an appropriate amount of Si3N4 (β phase, 1-3 μm Aladdin) and spread it flat in a crucible, and bake it at 500°C in a nitrogen atmosphere for 2 hours for subsequent use.
[0033] b. Prepare 0.01 mol·L -1 The Cu(NO3)2 solution is kept aside for later use.
[0034] c. Take an appropriate amount of Si3N4 preserved after step a, and place it at the focal position under the concentrated light of a 1000W xenon lamp; spray the prepared Cu(NO3)2 solution onto the surface of Si3N4 in small amounts and multiple times to load the active components on the semiconductor surface and remove excess moisture; control the Cu loading at 0.3%; then ultrasonicate it for 30 minutes to allow the metal ions to be evenly dispersed on the carrier surface, and then continue to dry the ultrasonicated catalyst at the focal position under the concentrated light of a 1000W xenon lamp for 10 minutes, and finally calcine it at 400°C in a muffle furnace for 2 hours to obtain the target catalyst Cu / Si3N4.
[0035] Embodiment 2:
[0036] a. Take an appropriate amount of Si3N4 (β phase, 1-3 μm Aladdin) and spread it flat in a crucible, and bake it at 500°C in a nitrogen atmosphere for 2 hours for subsequent use.
[0037] b. Prepare 0.01 mol·L -1 The Co(NO3)2 solution is kept aside.
[0038] c. Take an appropriate amount of Si3N4 preserved after step a, and place it at the focal position under the concentrated light of a 1000W xenon lamp; spray the prepared Co(NO3)2 solution onto the surface of Si3N4 in small amounts and multiple times to load the active components on the semiconductor surface and remove excess moisture; control the Co loading at 0.4%; then ultrasonicate it for 30 minutes to allow the metal ions to be evenly dispersed on the carrier surface, and then continue to dry the ultrasonicated catalyst at the focal position under the concentrated light of a 1000W xenon lamp for 10 minutes, and finally calcine it at 400°C in a muffle furnace for 2 hours to obtain the target catalyst Co / Si3N4.
[0039] Embodiment 3:
[0040] a. Take an appropriate amount of Si3N4 (β phase, 1-3 μm Aladdin) and spread it flat in a crucible, and bake it at 500°C in a nitrogen atmosphere for 2 hours for subsequent use.
[0041] b. Prepare 0.01 mol·L -1 Keep Fe(NO3)2 solution for later use.
[0042] c. Take an appropriate amount of Si3N4 preserved after step a, and place it at the focal position under the concentrated light of a 1000W xenon lamp; spray the prepared Fe(NO3)2 solution onto the surface of Si3N4 in small amounts and multiple times to load the active components on the semiconductor surface and remove excess moisture; control the Fe loading at 0.4%; then ultrasonicate it for 30 minutes to allow the metal ions to be evenly dispersed on the carrier surface, and then continue to dry the ultrasonicated catalyst at the focal position under the concentrated light of a 1000W xenon lamp for 10 minutes, and finally calcine it at 400°C in a muffle furnace for 2 hours to obtain the target catalyst Co / Si3N4.
[0043] Embodiment 4:
[0044] a. Take an appropriate amount of Si3N4 (β phase, 1-3 μm Aladdin) and spread it flat in a crucible, and bake it at 500°C in a nitrogen atmosphere for 2 hours for subsequent use.
[0045] b. Prepare 0.01 mol·L -1 Keep Ru(NO3)2 solution for later use.
[0046] c. Take an appropriate amount of Si3N4 preserved after step a, and place it at the focal position under the concentrated light of a 1000W xenon lamp; spray the prepared Ru(NO3)2 solution on the surface of Si3N4 in small amounts and multiple times to achieve the loading of active components on the semiconductor surface and remove excess moisture; control the loading amount of Ru at 0.3%; then ultrasonicate it for 30 minutes to allow the metal ions to be evenly dispersed on the surface of the carrier, and then continue to dry the ultrasonicated catalyst at the focal position under the concentrated light of a 1000W xenon lamp for 10 minutes, and finally calcine it at 400°C in a muffle furnace for 2 hours to obtain the target catalyst Ru / Si3N4.
[0047] Example 5
[0048] The performance of the catalyst was tested using an intermittent reaction system. CO2 and water vapor were used as reactants. In the initial state, 2 mL of H2O and 0.1 Mpa of CO2 were added to the reactor. 0.369 g of unloaded (i.e. pure) Si3N4 was weighed. The reactor volume was 100 mL. The light source for the reaction was a 1000 W xenon lamp. Under non-concentrating conditions, the reactor temperature was room temperature. The main product was a small amount of methane, which could not be quantified.
[0049] Embodiment 6:
[0050] An intermittent reaction system was used to test the performance of the catalyst. CO2 and water were used as reactants. In the initial state, 2mLH2O and 0.1MpaCO2 were added to the reactor. 0.19g of Si3N4 was weighed. The reactor volume was 100mL, and the light source for the reaction was a 1000W xenon lamp. The lens was used to focus the light, and the light was concentrated in the reactor as much as possible to promote the temperature increase of the reactants and catalysts in the reactor. Under the condition of high-speed heating, the surface temperature of the catalyst can reach up to 350 degrees. The temperature in the reactor rose rapidly through heat conduction, and the water inside the reactor turned into gas and reacted with CO2 on the catalyst surface. At the same time, the temperature was avoided from being too high, and the gas temperature was controlled at 250℃. After 3 hours of reaction, obvious hydrocarbons were produced. The main product was methane, with a yield of 21μmol·g -1 .
[0051] Embodiment 7:
[0052] An intermittent reaction system was used to test the performance of the catalyst. CO2 and water vapor were used as reactants. In the initial state, 2mLH2O and 0.1MpaCO2 were added to the reactor. The mass of Cu / Si3N4 was about 0.19g. The volume of the reactor was 100mL. The light source for the reaction was a 1000W xenon lamp. The light was focused by the lens. The light was concentrated in the reactor as much as possible to promote the temperature increase of the reactants and catalysts in the reactor. Under the condition of high-speed heating, the surface temperature of the catalyst can reach up to 350 degrees. The temperature in the reactor rose rapidly through heat conduction, and the water inside the reactor turned into gas and reduced with CO2 on the catalyst surface. At the same time, the temperature was avoided from being too high and the gas temperature was controlled at 250℃. After 3 hours of reaction, obvious hydrocarbons were produced. The main product was methane with a yield of 37μmol·g -1 .
[0053] Example 8
[0054] An intermittent reaction system was used to test the performance of the catalyst. CO2 and water vapor were used as reactants. In the initial state, 2mLH2O and 0.1MpaCO2 were added to the reactor. The mass of Fe / Si3N4 was weighed to be 0.19g. The volume of the reactor was 100mL. The light source used for the reaction was a 1000W xenon lamp. The light was focused by the lens, and the light was concentrated in the reactor as much as possible to promote the temperature increase of the reactants and catalysts in the reactor. Under the condition of high-speed heating, the surface temperature of the catalyst can reach up to 350 degrees. The temperature in the reactor rose rapidly through heat conduction, and the water inside the reaction turned into gas and reacted with CO2 on the catalyst surface for reduction. At the same time, the temperature was avoided to be too high, and the gas temperature was controlled to 250℃. After 3h of reaction, obvious hydrocarbons were produced. The main product was methane, with a yield of 26μmol·g -1.
[0055] Example 9
[0056] An intermittent reaction system was used to test the performance of the catalyst. CO2 and water vapor were used as reactants. In the initial state, 2mLH2O and 0.1MpaCO2 were added to the reactor. The mass of Co / Si3N4 was weighed to be 0.19g. The volume of the reactor was 100mL. The light source used for the reaction was a 1000W xenon lamp. The light was focused by the lens, and the light was concentrated in the reactor as much as possible to promote the temperature increase of the reactants and catalysts in the reactor. Under the condition of high-speed heating, the surface temperature of the catalyst can reach up to 350 degrees. The temperature in the reactor rose rapidly through heat conduction, and the water inside the reactor turned into gas and reacted with CO2 on the catalyst surface for reduction. At the same time, the temperature was avoided to be too high, and the gas temperature was controlled to 250℃. After 3h of reaction, obvious hydrocarbons were produced. The main product was methane, with a yield of 29μmol·g -1 .
[0057] Example 10
[0058] An intermittent reaction system was used to test the performance of the catalyst. CO2 and water were used as reactants. In the initial state, 2mLH2O and 0.1MpaCO2 were added to the reactor. The mass of Ru / Si3N4 was weighed to be 0.19g. The volume of the reactor was 100mL. The light source used for the reaction was a 1000W xenon lamp. The lens was used to focus the light. The light was concentrated in the reactor as much as possible to promote the temperature increase of the reactants and catalysts in the reactor. Under the condition of high-speed heating, the surface temperature of the catalyst can reach up to 350 degrees. The temperature in the reactor rose rapidly through heat conduction, and the water inside the reactor turned into gas and reacted with CO2 on the catalyst surface for reduction. At the same time, the temperature was avoided from being too high and the gas temperature was controlled to 250℃. After 3 hours of reaction, obvious hydrocarbons were produced. The main product was methane with a yield of 45μmol·g -1 .
[0059] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. The present invention can be improved in many aspects without violating the overall concept, and those familiar with the technology can modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by those with ordinary knowledge in the art without departing from the spirit and technical ideas disclosed by the present invention should still be covered by the claims of the present invention.
Claims
1. A high temperature semiconductor catalyst, characterized in that The high temperature semiconductor catalyst is prepared as follows: Placing Si3N4 at a focal position under a xenon lamp light source, spraying an aqueous solution of a transition metal salt onto the surface of the Si3N4 under a first irradiation to obtain the sprayed Si3N4; subjecting the sprayed Si3N4 to ultrasonic treatment for 20-40 minutes, continuing to place the sprayed Si3N4 at a focal position under a xenon lamp light source, irradiating it for a second time for 10-20 minutes, and calcining it at 300-500° C. in a muffle furnace for 1-3 hours to obtain the high-temperature semiconductor catalyst; The transition metal salt contained in the aqueous solution of the transition metal salt is nitrate, and the theoretical mass of the transition metal contained in the aqueous solution of the transition metal salt is 0.2%-0.5% of the sum of the theoretical mass of the transition metal contained in the aqueous solution of the transition metal salt and the mass of Si3N4; The total concentration of the transition metal salt in the aqueous solution of the transition metal salt is 0.01-0.1 mol·L -1 The transition metal contained in the aqueous solution of the transition metal salt is one or more of Fe, Cu, Co and Ru.
2. The high temperature semiconductor catalyst according to claim 1, characterized in that: The Si3N4 is β-phase Si3N4, and the particle size is 1 to 3 μm.
3. The high temperature semiconductor catalyst according to claim 1 or 2, characterized in that: The Si3N4 was also pretreated as follows: calcined at 500°C in a nitrogen atmosphere for 2 hours.
4. The high temperature semiconductor catalyst according to claim 1, characterized in that: The transition metal contained in the aqueous solution of the transition metal salt is Ru.
5. The high temperature semiconductor catalyst according to claim 1, characterized in that: The power of the xenon lamp light source is 1000W.
6. The high temperature semiconductor catalyst according to claim 1, characterized in that: The theoretical mass of the transition metal contained in the aqueous solution of the transition metal salt is 0.3%-0.4% of the total mass of the theoretical transition metal contained in the aqueous solution of the transition metal salt and Si3N4.
7. Use of the high-temperature semiconductor catalyst as claimed in claim 1 in the photothermal catalysis of CO2 and water to produce methane.
8. The use according to claim 7, characterized in that The application is: using a xenon lamp as a light source, focusing light in a closed reactor using a lens, using CO2 and water as reactants, and reacting under the high-temperature semiconductor catalyst to generate methane.
